Analisis Perbandingan Efesiensi Biaya dan Waktu pada Pondasi Sumuran dan Pondasi Tapak Pembangunan Gedung Tipikor Polda Aceh - Putri, Sandifa; Gunasti, Amri; Alihudien, Arief (Indonesian Journal Publisher, 2024)
The foundation is a building structure located under the building. The foundation cannot be separated from the building structure because it is a structural part whose function is to transmit the load from the upper structure to the supporting soil layer beneath it to prevent collapse of the soil or settlement of the structural system. This research compares the costs and time required for pit foundation work with site foundations, with the aim of finding out whether the planned costs and implementation time have the same efficiency or not. The purpose of this research is to find out how much bearing capacity there is in the well and site foundations, how much costs are needed to plan the well and site foundations, and how long the implementation time is required. The method used in this research is a comparative study (Comparison). The comparative or comparison method is research that uses the technique of comparing an object with another object. The objects being compared, the comparative method is carried out to compare the similarities and differences of two or more facts and properties of the object being studied. From the calculation analysis, the bearing capacity of the well foundation was obtained at 1950 KN with a cost of IDR 469,046,724 and an implementation time of 78 days. Meanwhile, for the site foundation, the foundation bearing capacity was obtained at 451.11 KN at a cost of IDR 174,598,298 and a construction time of 56 days.